Clinical and Echocardiographic Profile of Pediatric Patients with Ventricular Septal Defect: Echocardiographic Profile of Pediatric Patients having Ventricular Septal Defect - Munir, Roohi; Ahmad, Asif; Zaman, Anam; Wazir, Haseen Dil (Pakistan Journal of Health Sciences, 2025)
Ventricular septal defect (VSD) is the most common congenital heart disease in children, contributing significantly to pediatric morbidity and mortality globally. In resource-limited settings like Pakistan, delayed diagnosis and limited access to pediatric cardiology services can exacerbate disease outcomes. Objectives: To evaluate the clinical presentation and echocardiographic profile of pediatric patients diagnosed with VSD at a tertiary care center in Pakistan. Methods: This retrospective, cross-sectional descriptive study was conducted at the Department of Pediatric Cardiology of the Peshawar Institute of Cardiology from July 1, 2025, to September 31, 2025. A total of 200 children under 18 years of age with echocardiographically confirmed VSD were included. Data on demographics, clinical symptoms, and physical examination findings were collected. Echocardiographic assessment was used to determine the size, type, and location of VSD, along with associated cardiac anomalies. Results: The median age at diagnosis was 9.4 months, with 78% diagnosed within the first year of life. The most common presenting feature was cardiac murmur (60%), followed by recurrent respiratory infections (49%), feeding problems (42.5%), and failure to thrive (38%). Perimembranous VSD was the most prevalent type (62%), followed by muscular (19%), inlet (10%), and outlet (9%) defects. Associated cardiac lesions included patent ductus arteriosus (18%), atrial septal defect (14%), aortic valve prolapse (11%), and pulmonary hypertension (24%). Conclusions: Early recognition and echocardiographic screening, especially in high-risk groups like children with Down syndrome, are essential to improving outcomes. These findings support the need for enhanced screening and resource allocation in pediatric cardiology services in Pakistan.